The Implementation of Tasamuh ala Ahlussunah School in Learning Islamic Education: A Case in Ma’arif High School Purbalingga, Indonesia - Kamaludin; Muh Hanif (International Journal of Social Science and Religion (IJSSR), 2020)
The value of tasamuh as one of the values in Ahlussunah wal Jama’ah is very essential in implementation of Muslims. Tasamuh is to be tolerant of differences of views, especially in matters that are furuiyyah, so that they can coexist peacefully with other parties even though the aqeedah, way of thinking and culture are different. Tasamuh or mutual respect towards fellow Muslims is highly recommended in Islam to strengths in maintaining unity among Muslims, besides being a social demand it is also a form of brotherhood bound by the same aqeedah rope. Even in the hadith is explained that a person is not perfect in his faith if he does not have compassion and tolerance towards his Muslims brother. The aim of this research is to determine the exercise of the implementation of Tasamuh ala Ahlussunah wal Jama’ah in the learning of Islamic education in Ma’arif High School karanganyar Purbalingga and to know the inhibiting factors and supporting factors in the implementation of Tasamuh ala Ahlussunah in learning of Islamic education in Ma’arif High School Karanganyar, Purbalingga. The data collecting method used in this study are interview and documentation. Then, the data analysis used data reduction, presentation of data, and verification. The results of the research on the implementation of tasamuh ala Ahlussunah in learning Islamic education in Ma’arif High School Karanganyar include tasamuh attitudes towards fellow students, Tasamuh towards fellow Muslims and tasamuh towards non-Muslims. Supporting and inhibiting factors of the implementation of tasamuh ala Ahlussunah in learning Islamic education in Ma’arif High School Karanganyar is devided into two, namely internal factors and external factors.